A source of novelty and/or absurdity: the paradoxes of management. (26th February 2020) - Cunha, Miguel Pina e; Bednarek, Rebecca
This paper explores paradox, a way of seeing organisations that emphasises interdependence, opposition and persistence, as both a source of novelty and absurdity. Paradoxes are processes with a dual potential for organisational harm or good, depending on the way they are framed and tackled. We explore this dual side of paradox and discuss some of its implications for the management of organisations.